Myological variation in the forearm anatomy of Callitrichidae and Lemuridae. Issue 3 (20th May 2021) - Dickinson, Edwin; Boettcher, Marissa L.; Smith, Madison R.; Worden, Nikole A.; Swindell, Sidney R.; Seelye, Jason S.; Pastor, Francisco; Hartstone‐Rose, Adam
Abstract: The anatomy of the primate forearm is frequently investigated in terms of locomotor mode, substrate use, and manual dexterity. Such studies typically rely upon broad, interspecific samples for which one or two representative taxa are used to characterize the anatomy of their genus or family. To interpret variation between distantly related taxa, however, it is necessary to contextualize these differences by quantifying variation at lower hierarchical levels, that is, more fine‐grained representation within specific genera or families. In this study, we present a focused evaluation of the variation in muscle organization, integration, and architecture within two speciose primate families: the Callitrichidae and Lemuridae. We demonstrate that, within each lineage, several muscle functional groups exhibit substantial variation in muscle organization. Most notably, the digital extensors appear highly variable (particularly among callitrichids), with many unique configurations represented. In terms of architectural variables, both families are more conservative, with the exception of the genus Callimico —for which an increase is observed in forearm muscle mass and strength. We suggest this reflects the increased use of vertical climbing and trunk‐to‐trunk leaping within this genus relative to the more typically fine‐branch substrate use of the other callitrichids. Overall, these data emphasize the underappreciated variation in forearm myology and suggest that overly generalized typification of a taxon's anatomy may conceal significant intraspecific and intrageneric variation therein. Thus, considerations of adaptation within the forearm musculature should endeavor to consider the full range of anatomical variation when making comparisons between multiple taxa within an evolutionary context. Abstract : Photographs taking during the dissection of a specimen of Varecia rubra. (a) and (b) show superficial images of the anterior (flexor) and posterior (extensor) compartments; (c) and (d) show deeper images of the same compartments